2000
DOI: 10.1074/jbc.275.2.999
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Osteocalcin Transcription Involves Interaction of Protein Kinase A- and Protein Kinase C-dependent Pathways

Abstract: Osteocalcin is a major noncollagenous protein component of bone extracellular matrix, synthesized and secreted exclusively by osteoblastic cells in the late stage of maturation, and is considered indicator of osteoblast differentiation. Osteocalcin expression is modulated by parathyroid hormone (PTH) and a variety of other factors. The cAMP-dependent protein kinase pathway has been shown previously to have an essential role in PTH signaling and regulation of osteocalcin expression. To determine the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…In vitro, PTH inhibits bone marker gene expression and mineralization in differentiated osteoblasts and cementoblasts (49,56). In contrast, PTH rapidly induces osteoblastspecific gene expression in undifferentiated, proliferating osteoblasts (8,16,57,58). Thus, PTH may preferentially stimulate osteoblast differentiation in immature cells while inhibiting it in more mature cells.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, PTH inhibits bone marker gene expression and mineralization in differentiated osteoblasts and cementoblasts (49,56). In contrast, PTH rapidly induces osteoblastspecific gene expression in undifferentiated, proliferating osteoblasts (8,16,57,58). Thus, PTH may preferentially stimulate osteoblast differentiation in immature cells while inhibiting it in more mature cells.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
“…For example, Boguslawski et al (16) showed that PKA and PKC pathways cooperatively interact in PTH-mediated OCN gene expression in rat and human osteoblast cell lines. Consistent with these reports, the present study shows that these two pathways are also required for PTH-induced mouse OCN gene expression in MC3T3-E1 preosteoblast cells.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
See 1 more Smart Citation
“…via cAMP and forskolin [23]. In contrast, numerous studies have implicated this pathway in adipogenic differentiation.…”
mentioning
confidence: 95%
“…some amines derived from thyroid hormone decarboxylation and deiodination, known as thyronamines, have been shown to be endogenous compounds that stimulate caMP production via activation of Taar1 [36]. Cyclic aMP signaling regulates both osteogenic and apoptotic events [37,38]. VEdi-1 and thyronamines have a common basic chemical structure, thus we set out to determine whether VEdi-1 affects caMP production in osteoblasts.…”
Section: Acknowledgmentsmentioning
confidence: 99%